Tipologi, Tahapan Inovasi Dalam Pelayanan Publik: Pendekatan Fokus Dan Lokus Dalam Analisis Faktor Kunci Keberhasilan - Mozin, Sri Yulianty; Ma’ruf, Riskawati; Kadir, Fitra (JPS: Journal of Publicness Studies, 2025)
Innovation in public services is an urgent necessity for modern bureaucracy to respond to societal dynamics, technological shifts, and demands for transparency. This article examines the typology and stages of public service innovation through the lenses of "focus" (innovation types: technological, process, policy) and "locus" (levels of government: national, local, and implementation units) to analyze the key success factors. The method used is a systematic literature review of 42 scholarly articles and policy documents from the past decade. The findings indicate that innovation success is strongly influenced by leadership commitment, organizational capacity, public participation, and regulatory support. These results reinforce the innovation spiral theory and governance adaptability within the framework of bureaucratic reform. This study serves as a reference for designing contextually sustainable innovative policies in the Indonesian public sector.